Constructing a Climate Change Logic: An Institutional Perspective on the “Tragedy of the Commons” - Ansari, Shahzad (Shaz); Wijen, Frank; Gray, Barbara (Organization Science, 2013)
Despite increasing interest in transnational fields, transnational commons have received little attention. In contrast to economic models of commons, which argue that commons occur naturally and are prone to collective inaction and tragedy, we introduce a social constructionist account of commons. Specifically, we show that actor-level frame changes can eventually lead to the emergence of an overarching, hybrid “commons logic” at the field level. These frame shifts enable actors with different logics to reach a working consensus and avoid “tragedies of the commons.” Using a longitudinal analysis of key actors’ logics and frames, we tracked the evolution of the global climate change field over 40 years. We bracketed time periods demarcated by key field-configuring events, documented the different frame shifts in each time period, and identified five mechanisms (collective theorizing, issue linkage, active learning, legitimacy seeking, and catalytic amplification) that underpin how and why actors changed their frames at various points in time—enabling them to move toward greater consensus around a transnational commons logic. In conclusion, the emergence of a commons logic in a transnational field is a nonlinear process and involves satisfying three conditions: (1) key actors view their fates as being interconnected with respect to a problem issue, (2) these actors perceive their own behavior as contributing to the problem, and (3) they take collective action to address the problem. Our findings provide insights for multinational companies, nation-states, nongovernmental organizations, and other stakeholders in both conventional and unconventional commons.